A review of vaginal hysterectomies in the gynaecology department of a tertiary care hospital - Tayyiba Wasim; Gul e Rana; Zunair, Javeria; Nasrin, Tahira; Irshad, Sonia (Journal of the Pakistan Medical Association, 2024)
This retrospective cohort study analysed the trends and complications of vaginal hysterectomy conducted at Services Hospital, Lahore, from January 1, 2015 to December 31, 2020. Demographics, indications, surgery duration, complications (haemorrhage, urological or rectal problems, infection), and hospital stay were recorded. Out of 819 hysterectomies performed for benign gynaecological conditions, 112 (13.68%) were vaginal hysterectomies. Non-descent vaginal hysterectomy (NDVH) accounted for 33(29.46%) and uterine prolapse for 79(70.53%) of the cases. Mean age was 52.35 ±8.74 years, parity was 5.01±1.32, intraoperative haemorrhage was 796.87±450.1 ml, surgery duration was 48.61±12.28 minutes, and hospital stay was 2.58±0.41 days. Complications occurred in 19(16.97%) of the cases, while 93(83.03%) cases had no complications. Outcomes were comparable between NDVH and vaginal hysterectomy for prolapse (p=0.552). This indicates that vaginal hysterectomy is a safe procedure with minimal complications and quick recovery for uterine prolapse and non-descent uterus. However, a declining trend was observed over the study period.